Perspektiver for dansk udenrigspolitisk aktivisme Rasmus Brun Pedersen - Pedersen, Rasmus Brun (Politik, 2011)
In recent years ‘activism’ has been a defining character of Danish foreign policy. The article argues that there is more activism rather than a new form of active adaptation, as suggested in the Danish foreign policy literature. The argument is that different versions of activism have gradually replaced the reactive adaptation often associated with Danish foreign policy during the Cold War. Activism is not a well described concept in the Danish foreign policy tradition, however. The article argues that activism as a foreign policy strategy has some basic defining features but also that activism has developed through different phases after the end of the Cold War.